ZEW-EviSTA: A microsimulation model of the German tax and transfer system - Florian Buhlmann; Michael Hebsaker; Tobias Kreuz; Jakob Schmidhäuser; Sebastian Siegloch; Holger Stichnoth (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
This article describes ZEW-EviSTA®, the microsimulation model developed and used at ZEW - Centre for European Economic Research in Mannheim. The model simulates the German tax and transfer system using household micro level data. By estimating fiscal effects, labor market outcomes as well as distributional impacts the model allows for a comprehensive ex ante analysis of reform proposals. Heterogeneity analyses targeting specific subgroups of the population are feasible, too. The present article describes which data sources are used for the simulation, how key features of the German tax and transfer system are implemented, which simulation methods are employed to analyze policy changes and how the model is validated against official statistics. Moreover, by providing examples of the outputs which ZEW-EviSTA generates the paper gives an idea of the questions that can be answered using the model.
Keywords: D58; H20; J22; J23; 330; microsimulation; tax system; tax policy; labour market; labour supply; labourdemand; Germany; policy analysis